Annotated List of Orchidaceae for Myanmar - Ormerod, Paul; Kurzweil, Hubert; Watthana, Santi (Phytotaxa, 2021)
A list of all Orchidaceae recorded for Myanmar is presented, primarily based on many years of research in herbaria and libraries around the world, supplemented by recent fieldwork in various parts of Myanmar. As such, it is intended to form the basis for a treatment of Orchidaceae in the new flora of Myanmar project. A total of 1037 species in 152 genera is listed, which includes a number of uncertain identifications and indicates the need for further research. In addition, for four taxa occurrence in Myanmar is also suspected, but the available herbarium and literature information is not conclusive in this regard. The total number is comparatively low relative to neighbouring Thailand but expected to rise, given the fact that biodiversity is currently poorly understood even though extensive inventory efforts are now under way. In the introduction, the orchid flora of Myanmar, phytogeographical affinities and endemism are discussed and illustrated by graphs and tables. Each species entry in the taxonomic section consists of the name, place of original description, type information (if from Myanmar), list of citations of Myanmar specimens examined and global distribution; specific notes under many species elaborate various taxonomic issues. Two new combinations are made here, and five lectotypes and one neotype are designated. Six species are definite new distribution records for Myanmar, whereas identification of another three needs to be confirmed.